Nurses' attitudes towards diabetes in tertiary care: A cross‐sectional study - Ali Hassan Alhaiti; Mohammed Senitan; Selvanaayagam Shanmuganathan; Cliff Dacosta; Linda Katherine Jones; George Binh Lenon (Wiley, 2019)
Abstract Aim To evaluate the attitude and training of nurses in Saudi Arabia towards the care of patients with diabetes. Design A cross‐sectional study. Methods Data were collected in 2016 from 1,695 participants at the King Fahad Medical City using the Diabetes Attitude Scale version 3. Results Most nurses had not received diabetes training. The agreement score of nurses for the requirement of special training for the management of diabetes is high; the survey found that most nurses were aware of the psychological effect of diabetes. However, the low agreement regarding the perception of the seriousness of diabetes among nurses and the valuing of self‐care attributes such as tight control of glycaemic level in patients with diabetes indicates the need for diabetes training.